STUDY OF PIER UTILIZATION IN THE CILACAP FISHING PORT CENTRAL JAVA PROVINCE - Putri, Mulyani Indah; Syaifuddin, Syaifuddin; Zain, Jonny (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbtracPier is one of main facilities at Cilacap Fishing Port which is very needed for a port. The importance of the pier for fishing port can be seen by the pier’s separation according to the activities. The success of a fishing port in operational can be seen from the activities on the pier. The purpose of this study is to determine the utilization of the pier and the utilization rate of the pier at the Cilacap Fishing Port. This research has been conducted at Cilacap Fishing Port using survey method by conducting observation and direct interview with local port and fisherman. The results showed that the utilization of the pier at the Cilacap Fishing Port spesifically the I’s Pier has the utilization of loading and unloading pier for 105.66%, while the utilization rate of loading and unloading at II’s and the last is III’s Pier has the number of utilization rate about 121.27%. The percentage of utilization level of both pier is categorized as very well.Key words: Pier, Cilacap Fishing Port, Rate of Utilization.